Diagnosis and treatment of superior mesenteric artery compression syndrome complicated with gastroesophageal reflux disease. Issue 11 (5th June 2021) - Zhang, Rui; Li, Zhi-Tong; Han, Xin-Wei; Liang, Li-Dan; Wang, Zhong-Gao; Ji, Feng
Abstract : Supplemental Digital Content is available in the text